Management of Acute Kidney Injury and Extracorporeal Blood Purification Therapies During the COVID-19 Pandemic: The Italian SIN–SIAARTI Joint Survey (and Recommendations for Clinical Practice) - De Rosa, Silvia; Marengo, Marita; Romagnoli, Stefano; Fiorentino, Marco; Fanelli, Vito; Fiaccadori, Enrico; Brienza, Nicola; Morabito, Santo; Pota, Vincenzo; Valente, Fabrizio; Grasselli, Giacomo; Messa, Piergiorgio; et al. (Frontiers in Medicine, 2022)
Background and aim: The pandemic of Novel Coronavirus Disease 2019 is still challenging, given the large number of hospitalized patients who are at high-risk to develop AKI. For this purpose, we conducted a nationwide survey to assess incidence and management of AKI in critically ill patients affected by SARS-CoV-2 infection. Methods: This is a multicenter, observational, nationwide online survey, involving Italian Nephrology and Critical Care Units in Italy, developed in partnership between the Scientific Societies SIN and SIAARTI. Invitations to participate were distributed through emails and social Networks. Data were collected for 1 week during COVID-19 pandemic Results: A total of 141 responses were collected in the SIN-SIAARTI survey: 54.6% from intensivists and 44.6% from nephrologists. About 19,000 cases of COVID-19 infection have been recorded in hospitalized patients; among these, 7.3% AKI cases were observed, of which 82.2% in ICUs. Only 43% of clinicians routinely used the international KDIGO criteria. RRTs were started in 628 patients with a prevalence of continuous techniques with predominance in case of in case of oliguria (74.05%). An early start was preferred and RRT was excluded in case of therapeutic withdrawal and in the presence of severe co-morbidities or hemodynamic instability. Regional anticoagulation with citrate was the most common choice. The 41.04% of the physicians interviewed never used EBPT for inflammatory cytokine or endotoxin removal. Moreover, 4.33% of interviewed clinicians used these techniques only in AKI settings, whereas 24.63% adopted them even in the absence of AKI. Nephrologists made larger use of EBPT, especially in the presence of AKI. HVHF was never used in 58.54% of respondents; HCO membranes and adsorbents were used in more than 50% of cases. Conclusions: This joint SIN-SIAARTI survey among Italian Nephrology and Critical Care Units showed that during COVID-19 pandemic there was an underestimation of AKI based on the “non-use” of common diagnostic criteria, especially by intensivists. Likewise, the use of specific types of RRTs and in particular of blood purification therapies for immune modulation and organ support strongly differed among centers, suggesting the need for the development of standardized clinical guidelines.